(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
The surface of flat-sheet nylon membranes was modified using bisoxirane as the spacer and polyvinyl alcohol as the coating polymer. The amino acid histidine was explored as a ligand for endotoxins, aiming at its application for endotoxin removal from aqueous solutions. Characterization of the membrane adsorber, analysis of the depyrogenation procedures and the evaluation of endotoxin removal efficiency in static mode are discussed. Ligand density of the membranes was around 7 mg/g dry membrane, allowing removal of up to 65% of the endotoxins. The performance of the membrane adsorber prepared using nylon coated with polyvinyl alcohol and containing histidine as the ligand proved superior to other membrane adsorbers reported in the literature. The lack of endotoxin adsorption on nylon membranes without histidine confirmed that endotoxin removal was due to the presence of the ligand at the membrane surface. Modified membranes were highly stable, exhibiting a lifespan of approximately thirty months.